VO2MAX DAN KELINCAHAN SEBAGAI PREDIKTOR LITERASI FISIK DALAM KETERLIBATANNYA PADA KETERRAMPILAN JURUS TUNGGAL - Ali Mardius (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACT This study aims to analyze the impact of Vo2max and Agility as components of the main physical condition that affect the results of single skill skills. Fifty two pencak silat athletes (aged 20-23) from Padang City participated voluntarily in this study. Data regarding the measurement of VO2max of pencak silat athletes in the city of Padang, used the Multistage Fimess Test (MFT). The results of the measurement of the maximum oxygen uptake (VO2max) are recorded based on the shuttle level (rate) achieved by the athlete using the MFT Calculation Form, and the Agility of each pencak silat athlete in 2021 is used the SEMO Agility Test instrument. , as well as the Standard Single Kick skills used in this study is Form D-3. Furthermore, to examine the effect of this study, we took advantage of the IBM SPSS software. The results show that, there are differences in the correlation between men and women with the physical condition component of Vo2max and Agility with the skills to demonstrate a single move. The power of direct influence identified that higher VO max levels, in men than in women (r = 0.532 **, p <0.05) and agility (r = 0.483 **, p <0.05), had a significant positive effect on single skill skill. Therefore, the components of the physical condition of VO2max and agility are the main factors in the success of demonstrating single moves in the sport of pencak silat. The power of direct influence identified that higher VO max levels, in men than women (r = 0.532 **, p <0.05) and agility (r = 0.483 **, p <0.05), had a significant positive effect on single skill skill. Therefore, the components of the physical condition of VO2max and agility are the main factors in the success of demonstrating single moves in the sport of pencak silat. The power of direct influence identified that higher VO max levels, in men than in women (r = 0.532 **, p <0.05) and agility (r = 0.483 **, p <0.05), had a significant positive effect on single skill skill. Therefore, the components of the physical condition of VO2max and agility are the main factors in the success of demonstrating single moves in the sport of pencak silat. Keywords: Vo2Max, Agility, Single Kick